2022
DOI: 10.3389/fphar.2022.822499
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease Enhanced Tonic Inhibition is Correlated With Upregulated Astrocyte GABA Transporter-3/4 in a Knock-In APP Mouse Model

Abstract: Cognitive decline is a major symptom in Alzheimer’s disease (AD), which is strongly associated with synaptic excitatory-inhibitory imbalance. Here, we investigated whether astrocyte-specific GABA transporter 3/4 (GAT3/4) is altered in APP knock-in mouse model of AD and whether this is correlated with changes in principal cell excitability. Using the APPNL-F/NL-F knock-in mouse model of AD, aged-matched to wild-type mice, we performed in vitro electrophysiological whole-cell recordings combined with immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
3
3
1
Order By: Relevance
“…Studies have con rmed signi cantincreased GAT3/4 expression in astrocytes in hippocampus of APP knockout mouse model along with the enhancement of tonic inhibition [22].The excessive GABA and GABA transporter GAT3/4 was also observed in 5xFAD mouse model, and signi cantly enhanced tonic GABA inhibition and memory de cits in reactive astrocytes in the dentate gyrus (DG) of the hippocampus [23]. According to our TMT results, we con rmed that the upregulation of GAT3.…”
Section: Discussionsupporting
confidence: 68%
“…Studies have con rmed signi cantincreased GAT3/4 expression in astrocytes in hippocampus of APP knockout mouse model along with the enhancement of tonic inhibition [22].The excessive GABA and GABA transporter GAT3/4 was also observed in 5xFAD mouse model, and signi cantly enhanced tonic GABA inhibition and memory de cits in reactive astrocytes in the dentate gyrus (DG) of the hippocampus [23]. According to our TMT results, we con rmed that the upregulation of GAT3.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, in the hippocampus of the 5xFAD mouse model of AD, both GABA synthesis and release via GAT3 are specifically facilitated in reactive astrocytes, but not in neurons [28]. Similar results were obtained in another model of AD, the APP NL−F/NL−F knock-in mouse model [91]. Moreover, in this case, both GABA content and GAD67 expression are significantly increased in reactive astrocytes, leading to the GAT3-mediated GABA release and increased tonic inhibition of principal neurons in the CA1 and DG regions of the hippocampus [91].…”
Section: Gaba Release From Astrocytes In Disease 41 Alzheimer's Diseasesupporting
confidence: 76%
“…[35] reported that the Best1 silencing by means of shRNA blocks GABA release in the 5xFAD AD mouse model as well, which also suggests the Best1-mediated GABA release in this AD mouse model. These results contradict the GAT3-mediated release reported by Wu et al and Aldabbagh et al [28,91]. Unfortunately, this contradiction was not discussed in this publication.…”
Section: Gaba Release From Astrocytes In Disease 41 Alzheimer's Diseasecontrasting
confidence: 75%
See 1 more Smart Citation
“…Alzheimer's disease (AD) is the most common form of dementia and neurodegenerative condition in humans, with close to two‐thirds of all patients diagnosed with dementia being attributed to the onset of the disorder [ 1 ]. The cellular hallmarks of AD including, increased levels of both amyloid β (Aβ) deposition and neurofibrillary tangle formation, play an important function in activating neuroprotective mechanisms originating from both microglia and astrocytes, which after a certain point, begin to contribute towards the development of the pathogenesis associated with AD [ 2 , 3 ]. A consistent phenotype of AD that spans from human studies to various rodent models of AD is the abnormal synaptic hyperexcitation preceding phenotypic alteration of the disease, which has been noted as a relevant therapeutic target [ 4 , 5 , 6 ].…”
Section: An Overview Of Alzheimer's Disease and Network Dysfunctionmentioning
confidence: 99%